THE IMPACT OF SOCIAL CAPITAL ON RURAL HOUSEHOLD WELFARE IN MALAWI - Mtika, Natasha (PEOPLE: International Journal of Social Sciences, 2024)
Does cooperative membership promote household welfare? What are the determinants of social capital? What are the negative factors arising from social capital? By following a case study approach of two agricultural cooperatives in Malawi, the study focused specifically on rural household welfare to gain a deeper understanding of the mechanisms through which social capital impacts rural communities in Malawi. The empirical evidence gathered was directed to uncover social capital both as a determinant factor of household welfare as well as a household socio-demographic factor to capture both its exogeneity and its endogeneity. This research narrows the research gap in Malawi, since until this research, there remained a significant gap in the literature regarding the examination of the relationship between social capital and rural household welfare. This research, therefore, focuses specifically on the relationship between rural household income and social capital by using t-tests, also traditional regression analysis to determine the determinants of social capital. Results indicate that cooperative membership improves household welfare as revealed by the striking disparities in income levels and variability between cooperative members and non-cooperative members. This is attributed to the substantial economic benefits of cooperative membership such as reduced transactional costs and improved market and information access which are available to cooperative members as opposed to non-members, underscoring the role of social capital embedded in groups and cooperatives in contributing to the socio-economic development and poverty alleviation of rural households. Institutional trust, gender, and education emerged as key predictors of social capital underscoring the crucial roles of trust, gender dynamics, and education levels within social networks. This highlights the need for policy interventions that promote education, address gender disparities, and build people’s trust in local, district, and national institutions to enhance social capital among people in rural areas. Financial barriers, power imbalances, and leadership accountability were found to limit the inclusivity and accessibility of the networks by those who are outside as well as contribute to a lack of trust and reduced participation among members, especially those who feel marginalized or excluded.